Numeracy Gender Gap in STEM Higher Education: The Role of Neuroticism and Math Anxiety - Lunardon, Maristella; Cerni, Tania; Rumiati, Raffaella I. (Frontiers in Psychology, 2022)
The under-representation of women in Science, Technology, Engineering and Mathematics (STEM) is ubiquitous and understanding the roots of this phenomenon is mandatory to guarantee social equality and economic growth. In the present study, we investigated the contribution of non-cognitive factors that usually show higher levels in females, such as math anxiety (MA) and neuroticism personality trait, to numeracy competence, a core component in STEM studies. A sample of STEM undergraduate students, balanced for gender (NF = NM = 70) and Intelligent Quotient (IQ), completed online self-report questionnaires and a numeracy cognitive assessment test. Results show that females scored lower in the numeracy test, and higher in the non-cognitive measures. Moreover, compared to males’, females’ numeracy scores were more strongly influenced by MA and neuroticism. We also tested whether MA association to numeracy is mediated by neuroticism, and whether this mediation is characterized by gender differences. While we failed to detect a significant mediation of neuroticism in the association between MA and numeracy overall, when gender was added as a moderator in this association, neuroticism turned out to be significant for females only. Our findings revealed that non-cognitive factors differently supported numeracy in females and males in STEM programs.